`lim_(x->4)(f(x) - f(c))/(x-c)`

`lim_(x->4)(3/x - 3/4)/(x-4)`

` `Simplify expression:

`lim_(x->4)((12-3x)/(4x))/(x-4)`

`lim_(x->4)(3(4-x))/(4x(x-4))`

`lim_(x->4)(-(3/(4x))) = -3/16`

the alternate method to find the derivative of the function is the limit form.

**By limit process, the derivative of a function f(x) is :-**

**f'(x) = lim h --> 0 [{f(x+h) - f(x)}/h]**

Now, the given function is :-

f(x) = 3/x

thus, f'(x) = lim h --> 0 [{(3/(x+h)) - (3/x)}}/h]

or, f'x) = lim h --> 0 [{(3x - 3(x+h)}/{h*x*(x+h)}]

or, f'(x) = lim h --> 0 [-3h/{h*x*(h+x)}] = -3/{x*(x+h)}

putting the value of h = 0 in the above expression we get

f'(x) = -3/(x^2)

Thus, f'(c) = f'(4) = -3/(4^2) = -3/16

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now